Chemical Surface Modification Of Graphene Nanoplatelets By Carboxylation Process For Enhanced Sorption Capacities - Achutan, Rabita Mohd Firdaus (2019)
The aim of this thesis is to investigate the surface modification of carbon through chemical or physical attachment via carboxylation process for environmental remediation applications such as dye removal from wastewater. Chemical functionalization of graphene is required in many environmental applications and proper functionalization is an efficient approach to improve the adsorption capacity of graphene. Functionalized graphene nanoplatelet (fGNP) is a promising material for dye removal as this all-carbon nanomaterial possesses high specific surface area and has the ability to create a strong electrostatic interaction with a variety of oxygen-containing functional groups and π-electron systems. The effect of fGNP has not been widely explored, and many research groups worldwide have been focusing only on CNT, graphene, GO and rGO surfaces. In this thesis, a facile approach for the surface modification and fGNP were investigated. The approach involves fGNP with different type of acid and volumetric ratio acid to prove the best condition for greater dispersibility. Two type of acid used in this approach which are sulphuric acid and nitric acid. Their facile chemically modification by acid oxidation induces both facile dispersion in water and high adsorption capacity of methylene blue. Morphological, structural and chemical properties of the fGNP are deeply investigated by a set of complementary characterization techniques such as Fourier transformed infrared spectroscopy (FTIR), Scanning electron microscopy (SEM), High-resolution transmission electron microscopy (HRTEM), Thermogravimetric analysis (TGA) , Raman Spectroscopy and Zeta potential measurement. The BET surface areas raw GNP and functionalize GNP were in the range of 115-150 m2/g. Effects of temperature (30-60 °C), contact time (5 to 55 min), and initial dye concentration (25-200 mg/L) on adsorption performance of adsorbents were investigated. The maximum adsorption capacity of fGNPs increased from 112 mg/g to 151 mg/g at pH 4 and 60 °C. This can be directly linked to the increased of functional groups such as hydroxyl and carboxyl on the surface of modified adsorbents resulting in higher adsorption performance of fGNP. The equilibrium data gained were evaluated using isotherms, kinetic adsorption models and thermodynamic studies. For fGNP1 adsorbents, the isotherm data were significantly described by Langmuir model. The kinetic study revealed that the pseudo-first-order rate model was in better agreement with the experimental data. The values of the thermodynamic parameters, including ΔG0 (9.39,9.21 and 9.45 for temperature 30°C., 45°C, and 60 °C respectively), ΔH0 (8.85 kJ/mol) and ΔS0 (−1.57 kJ/mol). From the results, fGNP showed that MB adsorption is a spontaneous and endothermic process.